AXILLARY BRACHIAL PLEXUS BLOCK UNDER PROCEDURAL SEDATION FOR ARTERIOVENOUS FISTULA FORMATION IN A CHILD WITH END-STAGE RENAL DISEASE – A CASE REPORT: REGIONAL ANESTHESIA FOR ARTERIOVENOUS FISTULA FORMATION IN A CHILD - Jakšić, Lazar; serbian , serbian; serbian, serbian (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Arteriovenous (AV) fistula formation has become the gold standard for hemodialysis vascular access. The use of brachial plexus blocks (BPB) for antebrachial AV fistula formation in adults provides not just adequate analgesia but a potentially positive effect on primary fistula patency. Additionally, the resultant state of surgical anesthesia may enable the surgery to be performed under procedural sedation.  Case report: A 12-year-old patient was admitted for AV fistula formation for the purpose of hemodialysis due to end-stage renal disease. Kyphoscoliosis of the thoracic spine, the patient’s short neck with limited mobility, and her short stature posed a potential difficulty for intubation. Despite a recently resolved upper respiratory tract infection, which raised suspicion of airway hyperreactivity, the decision was made to proceed with surgical treatment and perform an axillary BPB under procedural sedation. Basic monitoring of vital functions was applied, with oxygen support at 3 l/min via mask. The ultrasound-guided block was performed using 8 ml of 0.5% levobupivacaine (1.4 mg/kg) and 5 ml of 2% lidocaine (3.33 mg/kg). During the one-hundred-minute surgical procedure, the patient maintained hemodynamic and respiratory stability and spontaneous breathing. The patient awoke without complications and was referred to the hospital ward. Her pain was managed with acetaminophen, as needed. The total perioperative opioid consumption was limited to the induction dose of 0.83 μg/kg of fentanyl.  Conclusion: In this pediatric case, the use of axillary BPB provided adequate analgesia with minimal opioid administration for the formation of an AV fistula. It also enabled the surgical team to avoid an expectedly difficult intubation. One needs to keep in mind the maximum safe dose of local anesthetics, the nuances of their use in children with comorbidities, as well as the potential complications, among which local anesthetic systemic toxicity is the most important.
Keywords: anesthesia; axillary brachial plexus block; pediatric case; hemodialysis; end-stage renal disease